Monitoring techniques for mechanical for mechanical expression using electrokinetic response caused by liquid flow through filter cake - Jami, Mohammed Saedi; Iwata, Masashi (2019)
In expression operation using filter-press of compression type, slurry material is filtered by pressure provided by a pump. When the chamber is filled with filter cake, the cake is expressed by the movement of the flexible diaphragm. The exact identification of the time that the chamber is filled with the cake is essential for the effective operation of the press. The electrokinetic response provides us with some information on the status of the filter chamber. In this work, we have measured the time course of electric potential difference (EPD) between the retaining walls during the whole process of expression to elucidate the electrokinetic aspects of mechanical dewatering. The experimental apparatus used in this study consists essentially of a piston press with a cylinder and a piston of 60 mm or 100 mm in diameter. Filter media are placed at the cylinder bottom and the very end of the piston. EPD between the filter media was monitored during the experiment. The absolute value of EPD increases with the progress of the filtration period, followed by the decrease during the consolidation period. It was observed that the time when the absolute value of the EPD began to decline coincides with the time when the filtration period ended. EPD reaches the first plateau value at the end of consolidation. In a consolidation of a homogeneous semisolid material, the absolute value of EPD increases at the beginning of the operation, followed by the decrease to the plateau value. We have derived the theoretical equation of streaming-potential for a flow path of the expressed material and combined it with filtration and consolidation theories to calculate the theoretical time course of EPD of expressed material. It has been found that EPD reflects liquid pressure variation throughout the solid/liquid mixture. Our findings can be used to monitor the progress of mechanical expression of various kinds of solid-liquid mixtures.